Group support systems features and their contribution to technology strategy decision-making: A review and analysis - Santos, Cláudio (2016)
Collective decision-making processes require careful design considerations in organizations. On one hand, the inclusion of a greater number of actors contribute to a wider knowledge base, on the other, it can become a diffuse process and be distorted from the principles initially established. This paper observes a specific collective decision making process in organizations—technology strategy formulation—and, through a critical review of the literature, analyzes how the advances in features of group support systems support improvements in different stages of this process. This paper also discusses the implications of GSS appropriation in group dynamics.